The effectiveness of emotion-focused couple therapy on decrease of marital burnout and depression of couples - Bahrami Moqadam, Mehdi; Afshariniya, Karim; Kakabaraee, Keivan (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: Couples always face very serious challenges as marital burnout and depression in their married lifein life. These problems can affect different aspects of their lives. The purpose of this study was to effectiveness of emotion-focused couple therapy on decrease of marital burnout and depression of couples. Methods: This quasi-experimental study was conducted with a pretest-posttest design with control group and follow-up 2 month. The statistical population of this research was all the couples who referred to counseling centers and psychological services in Kermanshah city in 2021. In the first stage, using convenience sampling method, 30 couples were selected and then randomly divided into 1 experimental group (15 couples) and 1 control group (15 couples) were replaced and experimental group underwent emotion-focused couple therapy (10 sessions 90 minutes), but the control group received no training and remained in the waiting list. To collect data marital burnout questionnaire of Pines (2003) and depression inventory (BDI-II) of Beck and et al (1996). Data analysis was performed using SPSS-24 software in two sections: descriptive and inferential (analysis of variance with repeated measures and Bonferroni). Results: The results of the study showed that of emotion-focused couple therapy in post-test and follow up had a significant effect on decrease of marital burnout and depression of couples (P<0.05). Conclusion: Based on the results of the present study, it can be said that emotion-focused couple therapy can be used as a treatment method to on decrease of marital burnout and depression of couples in counseling centers and family psychological services.